2006
DOI: 10.1007/s10661-006-8716-9
|View full text |Cite
|
Sign up to set email alerts
|

Metal Pollution in the Environment of Minas Gerais State – Brazil

Abstract: Intense mining activities in Minas Gerais State - Brazil brings out tons of waste to the environment. Considerable concentrations of toxic elements penetrate the soil, ground waters and rivers. This endangers the environment quality not only in the surrounding areas but also in ichthyofauna and in more distant areas of cattle raising and agricultural activities. After seasonal floods, veterinary clinic studies have shown that most animals raised in this region are affected by symptomatologic nervous diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Concentrations between 2.2 and 105 μg L −1 were found, and according to the authors, the principal form of human contamination in the region is likely due to the ingestion of contaminated dust, fish, and water (Matschullat et al 2000;Deschamps and Matschullat 2007). The presence of toxic metals in water and sediments has also been reported by Veado et al (2006) and Pereira et al (2007).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Concentrations between 2.2 and 105 μg L −1 were found, and according to the authors, the principal form of human contamination in the region is likely due to the ingestion of contaminated dust, fish, and water (Matschullat et al 2000;Deschamps and Matschullat 2007). The presence of toxic metals in water and sediments has also been reported by Veado et al (2006) and Pereira et al (2007).…”
Section: Introductionsupporting
confidence: 65%
“…The most abundant sulfide minerals are pyrite (FeS 2 ), arsenopyrite (FeAsS), and pyrrhotite (Fe 1−x S) (Matschullat et al 2000;Vial et al 2007), yet trace metal sulfides occur in subordinate phases as well (Gonçalves et al 2007). Previous studies have revealed high levels of arsenic (Matschullat et al 2000;Deschamps et al 2002;Borba et al 2003;Veado et al 2006;Deschamps and Matschullat 2007;Gonçalves et al 2007;Pereira et al 2007) in aquatic and terrestrial environments in different regions of the IQ. According to Deschamps et al (2002), such high amounts of arsenic in water, soils, and sediments in the IQ is related to both natural causes as well as past and recent mining activities.…”
Section: Introductionmentioning
confidence: 94%
“…Other American countries with an important long mining tradition have assessed soil contamination in the vicinity of mines such as those of San Luis de Potosí in Mexico [58] or Santa Barbara [59]. Contamination by trace elements from Minas Gerais (Brazil) has been found to seriously affect the local flora and fauna within a range of 400 km [60].…”
Section: Problems In Agricultural Soils Affected By Sulfide Miningmentioning
confidence: 99%
“…Such limitation was noted to bear substantial implications for the post-Kyoto discussion. The situation was found to be exacerbated on both hemispheres by enhanced nitrogen deposition from agricultural practices (in addition to combustion of fossil fuels; Bytnerowicz et al, 2013;Kozovits and Bustamante, 2013) and regionally by heavy-metal pollution from open-pit mining (such as in the State of Minas Gerais, Brazil;Veado et al, 2006). A research gap was identified in understanding air pollution effects, as part of climate change, on natural and managed forest and woodland ecosystems.…”
mentioning
confidence: 99%